Swine colibacillosis: global epidemiologic and antimicrobial scenario - Barros, Maria Margarida (2023)
Swine pathogenic infection caused by Escherichia coli, known as swine colibacillosis, represents an epidemiological challenge not only for animal husbandry but also for health authorities. To note, virulent E. coli strains might be transmitted, and also cause disease, in humans. In the last decades, diverse successful multidrug-resistant strains have been detected, mainly due to the growing selective pressure of antibiotic use, in which animal practices have played a relevant role. In fact, according to the different features and particular virulence factor combination, there are four different pathotypes of E. coli that can cause illness in swine: enterotoxigenic E. coli (ETEC), Shiga toxin-producing E. coli (STEC) that comprises edema disease E. coli (EDEC) and enterohemorrhagic E. coli (EHEC), enteropathogenic E. coli (EPEC), and extraintestinal pathogenic E. coli (ExPEC). Nevertheless, the most relevant pathotype in a colibacillosis scenario is ETEC, responsible for neonatal and postweaning diarrhea (PWD), in which some ETEC strains present enhanced fitness and pathogenicity. To explore the distribution of pathogenic ETEC in swine farms and their diversity, resistance, and virulence profiles, this review summarizes the most relevant works on these subjects over the past 10 years and discusses the importance of these bacteria as zoonotic agents.